Buddhism for all, not just for monks: Ideal society of Theravada Buddhism represented in Indonesian textbooks “Buddha’s biography for children” - Buaban, Jesada (RUSAMILAE JOURNAL, 2025)
This paper investigates the interpretation and representation of Theravada Buddhism in Indonesia through an analysis of the books Buddha’s Biography for Children, published respectively by the monastic group Sangha Theravada Indonesia (STI) and the lay scholars of the Ehipassiko Foundation. Using textual analysis as the research method, the data are conceptualized within the framework of ‘Engaged Buddhism’. The findings reveal that Sangha Theravada Indonesia, influenced by Thai Theravada Buddhism and Wat Bowornives Vihara, represents Theravada values by positioning monks at the center of Buddhist society, whereas the lay scholars ground their narratives in the Pali scriptures and decentralize the leading role of monks. In essence, while the monastic group seeks to preserve the charismatic image of the Buddha and monks, the lay scholars reinterpret Buddhism by portraying the Buddha as an ordinary person engaged in social welfare, thereby aligning Buddhist representation with the needs and values of modern society.